Chronic high-fat diet consumption induces an alteration in plasma/brain neurotensin signaling, metabolic disturbance, systemic inflammation/oxidative stress, brain apoptosis, and dendritic spine loss - Napatsorn Saiyasit (2020)
© 2020 Elsevier Ltd Chronic high-fat diet (HFD) consumption caused not only negative effects on obesity and metabolic disturbance, but also instigated several brain pathologies, including dendritic spine loss. In addition, alterations in plasma/brain neurotensin (NT) levels and NT signaling were observed in obesity. However, the mechanistic link between the NT levels in plasma and brain, NT signaling, and peripheral/brain pathologies following prolonged HFD consumption still needs to be elucidated. We hypothesized that an increase in peripheral/brain NT signaling were associated with peripheral/brain pathologies after prolonged HFD consumption. Male Wistar rats (n = 24) were given either a normal diet (ND) or a HFD for 12 and 40 weeks. At the end of each time course, metabolic parameters and plasma NT levels were measured. Rats were then decapitated and the brains were examined the levels of brain NT, hippocampal reactive oxygen species, the number of Iba-1 positive cells, the dendritic spine densities, and the expression of NT-, mitophagy-, autophagy-, and apoptotic-related proteins. The findings showed an increase in the level of plasma NT with dyslipidemia, metabolic disturbances, systemic inflammation/oxidative stress, and hippocampal pathologies in rats fed HFD for 12 and 40 weeks. The expression of brain NT signaling and brain apoptosis were markedly increased after 40 weeks of HFD feeding. These results indicated that the alteration in the level of circulating/brain NT and its downstream signaling were associated with central and peripheral pathologies after long-term HFD intake. Therefore, these alterations in NT level or its signaling could be considered as a therapeutic target in treating obesity.